Biblical law, royal decrees and jurisdiction: linguistic and historical perspectives - Angelini, Anna; Vergari, Romina (Semitica et Classica, 2024)
Abstract This introductory essay sets the research topics addressed in this dossier, namely the study of the processes of adaptation and rewriting of law in the Hebrew Bible, in the Septuagint and in the broader context of the legal traditions of the ancient Near East and the Greco-Roman milieu. It highlights, moreover, the potential that a contrastive analysis of different corpora (especially the Septuagint and Judeo-Hellenistic literature), provides to this line of research, considering that in this period not only the Jews had to deal with foreign powers and different legal systems, both in Judea and in the diaspora, but also that the question of the type of authority exercised by Jewish law became increasingly central and salient in the discourse of its interpreters. Finally, it examines the specific contribution of each article to the set research questions. Abstract Cette introduction définit les thèmes de recherche abordés dans ce dossier, à savoir l’étude des processus d’adaptation et de réécriture du droit dans la Bible hébraïque, dans la Septante et dans le contexte plus large des traditions juridiques du Proche- Orient ancien et de l’époque gréco-romaine. Elle souligne, en outre, l’importance que peut donner à cet axe de recherche une analyse contrastée de différents corpus, en particulier la Bible des Septante et la littérature judéo-hellénistique, compte tenu du fait qu’à cette époque non seulement les juifs étaient confrontés à des puissances étrangères et à des systèmes juridiques différents, tant en Judée que dans la diaspora, mais aussi que la question du type d’autorité exercée par la loi juive est devenue de plus en plus centrale et saillante dans le discours de ses interprètes. Enfin, elle examine la contribution spécifique de chaque article aux questions de recherche posées.